Pengaruh Kompetensi Sumber Daya Manusia, Sistem Pengendalian Internal, dan Kualitas Sistem Informasi Terhadap Pengelolaan Aset Tetap: Studi Kasus pada Pemerintah Daerah Kabupaten Bandung - Hani Noviani; Heni Nurani Hartikayanti (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the influence of human resource competence, internal control system, and information system quality on fixed asset management at Bandung Regency Government. This research uses a quantitative approach with survey method through questionnaires. The research population consists of asset managers in Regional Work Units (SKPD) in Bandung Regency with a sample of 60 respondents selected using purposive sampling technique. Data were analyzed using multiple linear regression analysis with SPSS software. The results show that: (1) Human resource competence does not have a significant effect on fixed asset management; (2) Internal control system has a significant positive effect on fixed asset management; (3) Information system quality has a significant positive effect on fixed asset management; and (4) Simultaneously, human resource competence, internal control system, and information system quality have a significant effect on fixed asset management at Bandung Regency Government. The coefficient of determination test results show that the three independent variables are able to explain variations in fixed asset management, while the rest is influenced by other factors not examined in this study.